KEPENTINGAN PEMERINTAH URUGUAY MELEGALISASI GANJA PADA MASA PEMERINTAHAN JOSE ALBERTO MUJICA CORDANO TAHUN 2010-2015 - Pebrianto Nainggolan; Den Yelta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study explain about Uruguay government interests to legalization marijuana in the reign of Jose Alberto Mujica Cordano in 2013. Uruguay is a first country who legalize cultivation, distribution, and consumtion of marijuana in the world. Marijuana is plant which producing a fiber, but better known as narcotic substance in the seeds that can make the user feeling pleasure without cause. This regulation was first proposed by Jose Alberto Mujica Cordano and approved by parlament and senate. This study shows Uruguay government interest to legalization marijuana for politics interests and economy interests. Political interest are combating illegal marijuana syndicate, controlling the market and consumtion of marijuana, opening job vacancy, and reduce social problem. And the economic interest are getting benefit from the tax and reducing state spending. This policy was criticized by INCB ( The International Control Board) becauseUruguay belong participate country to signature The Single Country Convention of 1961.Keywords: Marijuana, Legalization, Regulation, Government, politics interests and economy interests.